Controle biológico do pulgão de trigo Sitobion avenae (Fabricius 1775) pelo parasitóide Aphidius colemani Viereck, 1912 em Medianeira, PR, Brasil - Zanini, Agostinho (2004)
Historically, aphids were the main phytosanitary problem in the production of winter cereals in de 70 s in southern Brazil. Attacking intensively during wheat s emergence to the affiliation, it s usually fatal to the plant. However, these bugs possess important population suppression that, although considered the most efficient and specific, had a frail role in aphid natural biological control in wheat production in Brazil where chemical control became necessary to prevent production loss. Thereby, in 1978 14 species of exotic parasites were introduced in Brazil aiming plaque control, and in 1984 the West of Parana s Biological Control Program was introduced when 4 species were released. Along the years, it provided an aphid population reduction and consequently the reduction on chemical applications. The reason of this study is because no bibliographic studies referring to the settlement of the parasite in the west of Paraná s region was found. A weekly sampling, in twenty-five 25 m2 parcels, of 100 wheat plants was taking where the aphids and mummies were removed. A single aphid specie, Sitobion avenae (Fabricius), was found, the primary parasite Aphidius colemani (Vierek 1912), and hyper-parasites. It was also detected the presence of predators. Population summit of S. avenae occurred at the beginning of blossoming and mummies showed up a week following the aphids. Parasite emergence was observed in 34% of the collected mummies, 29.4% of hyper-parasites, and no emergence was found in 36.6% of the total. Aphid control was found to be excellent, because as their population increased so did the parasite A. colemani level, reaching its population peak in early August with 37.2%. Hyper-parasites reached population peak in mid-August, and predator number was lower than the number of parasites. Considering the number of parasites released, 14 different species altogether, and the fact that only one species in 2003 was found indicates that probably, in the west of Paraná s region, conditions were not favorable to the other 13 but to A. colemani